THE SALT POTENTIALS IN INDONESIA - Sukiyah, Emi; Isnaniawardhani, Vijaya; Sudradjat, Adjat; Muhamadsyah, Faisal (Journal of Geological Sciences and Applied Geology, 2017)
Abstract The salt deposits are unevenly distributed in the world. The most productive countries are China, USA and India. Indonesia experiences the salt deficit, due to the limited number of the deposits. The evaluation of the characteristics of salt deposit in the world reveals the Pre Tertiary association in semi closed marine environmental deposition. The geological condition in Indonesia does not favor such environment, therefore the salt deposits unlikely to occur. The saline solution in mud volcanoes in northern part of Java Island however indicates the possible saline deposits in Tertiary Kalibeng Formation with the thickness of approximatelly 3.000 meters. The saline seepages most probably have continuously been taking place since early Pleistocene or about a million years ago. The saline seepages in northern part of East Java might extend to thebottom of Madura Strait and enrich the salinity of the sea in the strait. The semi closed configuration of the strait contributes to the accumulation of salt. It is therefore suggested to expand the evaporating pools for salt production, among others by the reclamation of the shallow offshore area in the southern part of the island. Keywords: salt deficit, mud volcano, saline solution, enrich the salinity, solar evaporating pools